The Shrunken, Bright Cerebellum: A Characteristic MRI Finding in Congenital Disorders of Glycosylation Type 1a - Feraco, P.; Mirabelli-Badenier, M.; Severino, M.; Alpigiani, M.G.; Di Rocco, M.; Biancheri, R.; Rossi, A. (American Journal of Neuroradiology, 2012)
SUMMARY: CDG-1a is an early-onset neurodegenerative disease with selective hindbrain involvement and highly variable clinical presentation. We retrospectively reviewed the clinical records and MR imaging studies of 5 children (3 boys and 2 girls aged 12 days to 2 years at presentation) with molecularly confirmed CDG-1a. The cerebellum was hypoplastic at presentation in 4 cases, progressive bulk loss involved the cerebellum and the pons in all cases, and the cerebellar cortex and subcortical white matter were hyperintense on T2-weighted and FLAIR images in all. We conclude that CDG-1a likely results from a combination of cerebellar hypoplasia and atrophy. Cerebellar volume loss with diffuse T2/FLAIR hyperintensity seems to be a peculiar association in the field of cerebellar atrophies, and may be useful to address the differential diagnosis. BAEPbrain stem auditory evoked potentialCAcerebellar atrophyCDGcongenital disorders of glycosylationCHcerebellar hypoplasiaEEGelectroencephalogramERGelectroretinogrammInsmyo-inositolNCVnerve conduction velocityPMMphosphomannomutasePRESSpoint-resolved spectroscopy sequencesIscyllo-inositolVEPvisual-evoked potentials